AN ETHNOBOTANICAL EXPLORATION OF MEDICINAL PLANTS IN MANAR BEAT, KARAMADAI RANGE, WESTERN GHATS, TAMIL NADU - RAMYA EK; MOWNIKA S; SHARMILA S (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: This investigation provides an ethnobotanical information that truly focused on the traditional medicinal plants used by Irula community inhaled in Manar beat to treat various human diseases. Ethnobotanical study about medicinal plants was carried out from January 2018 to December 2018 in Manar beat, Karamadai range, Western Ghats, Tamil Nadu. Methods: The traditional in-depth knowledge of medicinal plants was collected during group discussion, interviews, and guided field walks along with tribe. All the traditional medicinal plants collected during the field visit were identified with local floras and the identity was authenticated by Botanical Survey of India. Results: A total of 89 medicinally important endemic, threatened and endangered aromatic herbal plants distributed in 71 genera and 42 families were collected and identified. Among the surveyed plants, Fabaceae and Moraceae with eight species were the largest plant families, respectively. Leaves (35%) are most widely used plant part of reported plants and decoction forms are mostly used by Irulas. The surveyed plants were checked for conservation status in Red Data List formulated by the International Union for Conservation of Nature; around nine species were listed out. Conclusion: The documentation of the medicinal herbal plants will be a good reference to all the young researches to carry out various conservation works.